Inner-biblical allusion in the poetry of Wisdom and Psalms - Boda, Mark J.; Chau, Kevin (Kevin D.); Tanner, Beth LaNeel, 1959- (London : T&T Clark, 2019)
"The contributors to this volume discuss not merely the theoretical aspects of the phenomenon of inner biblical allusion but rather provide practical examples of scholars working with specific texts within the Wisdom and Psalms corpora in order to showcase the function of this phenomenon within poetic texts. Closing responses from senior scholars (David Clines and John Goldingay) provide a critical engagement and mature reflection on the contributions."--Bloomsbury Publishing.
The Psalmist as historiographer / Jeffery M. Leonard -- Allusion or illusion in the Psalms : how do we decide? / Beth LaNeel Tanner -- Exodus 34.6 in Psalms 86, 103, and 145 in relation to the theological perspectives of Books III, IV, and V of the Psalter / Hee Suk Kim -- The elevation of God in Psalm 105 / David Emanuel -- The poetry of creation and victory in the Psalms / Kevin Chau -- A ridiculous God : Job uses Psalm 8.5 [4] to respond to Eliphaz / Charles Yu -- Poetic allusions in Agur's oracle in Proverbs 30.1-9 / Ryan P. O'Dowd -- The reuse of Deuteronomy's "Law of the vow" in Ecclesiastes 5.3-5 [4-6] as an exemplar of intertextuality and reinterpretation in Ecclesiastes 4.17-5.6 [5.1-5.7] / Richard L. Schultz -- Some reflections on interpreting allusion : the case of creation motifs in Isaiah / Job Y. Jindo.
Includes bibliographical references (pages 166-181) and index.
Also issued in print.
Electronic reproduction.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Comparative studies; Bible. -- Criticism, interpretation, etc; Allusions in the Bible